Interactive Alignment and Lexical Triggering of Code-Switching in Bilingual Dialogue - Kootstra, Gerrit Jan; Dijkstra, Ton; van Hell, Janet G. (Frontiers in Psychology, 2020)
When bilingual speakers use two languages in the same utterance, this is called code-switching. Previous research indicates that bilinguals’ likelihood to code-switch is enhanced when the utterance to be produced (1) contains a word with a similar form across languages (lexical triggering) and (2) is preceded by a code-switched utterance, for example from a dialogue partner (interactive alignment/priming of code-switching). Both factors have mostly been tested on corpus data and have not yet been studied in combination. In two experiments, we therefore investigated the combined effects of interactive alignment and lexical triggering on code-switching. In Experiment 1, Dutch-English bilinguals described pictures to each other in a dialogue game where a confederate’s code-switching was manipulated. The participants were free to use either Dutch, English, or a combination of Dutch and English in describing the pictures, so they could voluntarily code-switch or not. The pictures contained a cognate [e.g., roos (rose)], a false friend [e.g., rok (skirt, false friend with rock)], or a control word [e.g., jas (coat)]. Participants code-switched more often when the confederate had just code-switched (indicating interactive alignment). They also code-switched more often when cognates were involved, but only when the confederate had just code-switched. This indicates that lexical triggering is driven by interactive alignment. False friends did not enhance the likelihood of code-switching. Experiment 2 used a similar dialogue game with participants from the same population but focused specifically on how to account for interactive alignment of code-switching. Rather than aligning on their dialogue partner’s pragmatic act of code-switching, bilinguals aligned on the language activation from the utterance produced by their dialogue partner. All in all, the results show how co-activation of languages at multiple levels of processing together influence bilinguals’ tendency to code-switch. The findings call for a perspective on bilingual language production in which cross-speaker and cross-language processes are combined.